Polymeric Nanocarriers Autonomously Cross the Plant Cell Wall and Enable Protein Delivery for Stress Sensing - Zhang, Yilin; Cao, Yunteng; Jiang, Wenzhi; Ma, Qingquan; Shin, Jinwoo; Sun, Hui; Cui, Jianqiao; Chen, Yongsheng; Giraldo, Juan Pablo; Strano, Michael S.; Lowry, Gregory V.; Sheen, Jen; et al. (Advanced materials (Weinheim), 2024)
Delivery of proteins in plant cells can facilitate the design of desired functions by modulation of biological processes and plant traits but is currently limited by narrow host range, tissue damage, and poor scalability. Physical barriers in plants, including cell walls and membranes, limit protein delivery to desired plant tissues. Herein, a cationic high aspect ratio polymeric nanocarriers (PNCs) platform is developed to enable efficient protein delivery to plants. The cationic nature of PNCs binds proteins through electrostatic. The ability to precisely design PNCs’ size and aspect ratio allowed us to find a cutoff of ≈14 nm in the cell wall, below which cationic PNCs can autonomously overcome the barrier and carry their cargo into plant cells. To exploit these findings, a reduction‐oxidation sensitive green fluorescent protein (roGFP) is deployed as a stress sensor protein cargo in a model plant Nicotiana benthamiana and common crop plants, including tomato and maize. In vivo imaging of PNC‐roGFP enabled optical monitoring of plant response to wounding, biotic, and heat stressors. These results show that PNCs can be precisely designed below the size exclusion limit of cell walls to overcome current limitations in protein delivery to plants and facilitate species‐independent plant engineering. A cationic high aspect ratio polymeric nanocarrier is developed to deliver functional protein in crops to enable species‐independent plant engineering. The delivered sensor protein reduction‐oxidation sensitive green fluorescent protein (roGFP) successfully monitors stressors in tobacco, tomato, and maize. This functional protein delivery platform paves the way for new technologies in plant sensing and engineering, contributing to the design of new solutions that promote plant‐based sustainable development.